Perbedaan Kualitas Warna Kain Katun Primissima Menggunakan Zat Warna Gulma Kirinyu (Chromolaena Odorata L) dengan Zat Mordan Tawas dan Tunjung - Tri Rahayu (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2026)
The use of synthetic dyes in the textile industry has caused various environmental problems due to waste that is difficult to degrade and has the potential to contaminate water and soil. Therefore, the development of environmentally friendly natural dyes is an important alternative to be explored. One potential but underutilized source of natural dye is kirinyuh weed (Chromolaena odorata L.), which is known to contain natural pigment compounds such as tannins and flavonoids. This study aims to analyze the dyeing quality of primissima cotton fabric using kirinyuh leaf extract with variations of alum and ferrous mordants through a mordanting process. The research employed an experimental method, including hot extraction of kirinyuh leaves, dyeing of primissima cotton fabric, and mordanting using alum and ferrous salts. The evaluation of dyeing quality focused on washing color fastness and light color fastness tests based on standard textile testing methods. The results indicate that the type of mordant significantly affects the resulting color quality. Alum mordant produced relatively lighter colors with good washing fastness, while ferrous mordant resulted in darker shades with similarly good washing fastness. However, color fastness to light showed relatively lower values, particularly in fabrics treated with alum mordant. Based on these findings, it can be concluded that kirinyuh leaf extract has the potential to be used as a natural dye for primissima cotton fabric, although further optimization is required to improve color resistance to light exposure.